ENSAIO DE COMBATE AO CUPUM DE MONTE ð˜Šð˜°ð˜³ð˜¯ð˜ªð˜µð˜¦ð˜³ð˜®ð˜¦ð˜´ ð˜¤ð˜¶ð˜®ð˜¶ð˜ð˜¢ð˜¯ð˜´ (KOLLAR, 1832) COM CLORPIRIFÃ“S, FENTIOM E ÃGUA - Hamamura, R.; Rangel, R. C.; Regitano, E. B.; Mesquita, L. F.; Cardoso, M. A. C.; Clari, A. I.; Mariconi, F. A. M. (REVISTA DE AGRICULTURA, 2020)
ENSAIO DE COMBATE AO CUPUM DE MONTE ð˜Šð˜°ð˜³ð˜¯ð˜ªð˜µð˜¦ð˜³ð˜®ð˜¦ð˜´ ð˜¤ð˜¶ð˜®ð˜¶ð˜ð˜¢ð˜¯ð˜´ (KOLLAR, 1832) COM CLORPIRIFÃ“S, FENTIOM E ÃGUA